Separation of natural colorants from the fermented broth of filamentous fungi using colloidal gas aphrons - Santos-Ebinuma, Valéria Carvalho [UNESP]; Teixeira, Maria Francisca Simas; Pessoa, Adalberto; Jauregi, Paula (Elsevier, 2016)
There is a worldwide interest in the development of processes for producing colorants from natural sources. Microorganisms provide an alternative source of natural colorants produced by cultivation technology and extracted from the fermented broth. The aim of the present work was to study the recovery of red colorants from the fermented broth of Talaromyces amestolkiae using the technique of colloidal gas aphrons (CGA) comprising surfactant-stabilized microbubbles. Preliminary experiments were performed to evaluate the red colorants' solubility in different organic solvents, octanol/water partitioning, and their stability in surfactant solutions, namely hexadecyl trimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS), and polyoxyethylenesorbitan monolaurate (Tween 20), which are cationic, anionic and nonionic surfactants, respectively. The first recovery experiments were carried out using CGA generated by these surfactants at different volumetric ratios (VR, 3-18). Subsequently, two different approaches to generate CGA were investigated at VR values of 6 and 12: the first involved the use of CTAB at pH 6.9-10.0, and the second involved the use of Tween 20 using red colorants partially dissolved in ethanol and Tween 20. The characterization results showed that red colorants have a hydrophilic nature. The highest recoveries were obtained with Tween 20 (78%) and CTAB (70%). These results demonstrated that the recovery of the colorants was driven by both electrostatic and hydrophobic interactions. The VR was found to be an important operating parameter and at VR 12 with CTAB (at pH 9) maximum recovery, partitioning coefficient (K = 5.39) and selectivity in relation to protein and sugar (SP = 3.75 and SS = 7.20 respectively) were achieved. Furthermore, with Tween 20, the separation was driven mainly by hydrophobic interactions. Overall CGA show promise for the recovery of red colorants from a fermented broth. Although better results were obtained with CTAB than with Tween 20 the latter may be more suitable for some application due to its lower toxicity.
Keywords: Bioprocess; Colloidal gas aphron; Extraction; Natural colorants; Surfactants